Low‐power divide‐by‐five injection‐locked frequency divider with a built‐in balun. Issue 1 (13th August 2020) - Chang, Yu‐Hsin
Abstract: This paper reports an injection‐locked frequency divider (ILFD) with a divide‐by‐five feature, a built‐in balun, and low power consumption fabricated in a standard 0.18 μm CMOS process. By employing a fourth harmonic (4 f 0 ) enhancement technique realized in a stacked cross‐coupled pair and mixing with an injection signal (5 f 0 ) through injection transistors, an output signal ( f 0 = 5 f 0 ‐4 f 0 ) is obtained without using extra passive devices. The built‐in balun is employed to transfer a single‐ended signal to differential signals injected into injection transistors. The proposed ILFD improves the locking range without the help of varactors and the power dissipation by adopting two cross‐coupled transistor pairs. The proposed ILFD has the free‐running frequency of 4.3 GHz and the injection frequencies from 21.1 to 22.1 GHz at an input power level of 0 dBm. The proposed ILFD core only consumes 3.75 mW from a supply voltage of 1.5 V.